2015
DOI: 10.1002/pd.4561
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive prenatal testing for trisomy 21 based on analysis of cell‐free fetal DNA circulating in the maternal plasma

Abstract: Non-invasive prenatal test for trisomy 21 is a robust strategy that can be translated from seminal publications. Publicly funded studies should refine its indications and cost-effectiveness in prenatal screening and diagnosis. © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
(113 reference statements)
0
17
0
1
Order By: Relevance
“…Only studies with high or moderate quality were considered suitable to use for grading the quality of scientific evidence. Twenty‐two were assessed as low‐quality and were excluded from analysis (Table S2), leaving 31 articles (32 studies) for further analysis (Figure ) . Two other studies were excluded because they reported on the same patients as in Jensen et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only studies with high or moderate quality were considered suitable to use for grading the quality of scientific evidence. Twenty‐two were assessed as low‐quality and were excluded from analysis (Table S2), leaving 31 articles (32 studies) for further analysis (Figure ) . Two other studies were excluded because they reported on the same patients as in Jensen et al.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are summarized in Tables S3–S5. Twenty‐three studies were prospective cohort studies and nine were case‐control‐studies . The majority of sampling had occurred during the first trimester.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐invasive prenatal testing (NIPT) for fetal aneuploidies by second‐generation sequencing (SGS) has been commercially available since 2011 . Within the last couple of years, there has been a strong interest among non‐commercial public health labs to establish the test in local analytic settings . However, efficient implementation of NIPT is, apart from high equipment costs, impeded by the lack of publically available technical and bioinformatic guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of the BJD , two studies highlight potential biomarkers for EMPD; levels of serum cell‐free (cf)DNA) and a combination of serum cytokeratin 19 fragment 21‐1 (CYFRA) and serum carcinoembryonic antigen (CEA) . cfDNA is currently being studied in a range of fields from prenatal diagnosis of trisomy disorders, to its role as a diagnostic, prognostic and predictive biomarker in a host of cancer settings and refers to all nonencapsulated DNA in the bloodstream. CYFRA on the other hand is a fragment of cytokeratin 19, which forms an integral part of the epithelial cytoskeleton, whereas CEA is a cell surface glycoprotein.…”
mentioning
confidence: 99%